EKONOMI PANCASILA PADA GENERASI Z: TRANSFORMASI DIGITAL DAN INSTITUTIONAL TRUST - Aleknaek Martua; Meliasta Hapri Tarigan; Ardika Nurfurkon; Andi Pitono; Daniel E.L. Tarigan (Jurnal Politik Pemerintahan Dharma Praja, 2026)
This study aims to analyze the influence of property rights, digital transformation, and literacy on Generation Z’s institutional trust in cooperatives from the perspective of the Pancasila Economy. The study employs a quantitative approach using a survey method involving 300 Generation Z respondents in Indonesia. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of the study indicate that all constructs meet the criteria for validity and reliability. Digital transformation was found to have a positive effect on literacy and trust, while literacy also has a significant effect on trust. In addition, property rights have a strong influence on digital transformation and trust, both directly and indirectly through the mediating effect of literacy. These findings suggest that strengthening digital-based cooperative governance can increase Generation Z’s trust in cooperatives in the digital economy era.